2017
DOI: 10.1155/2017/2412890
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Genomic Targets of Neural Stem Cells for Functional Recovery after Hemorrhagic Stroke

Abstract: Hemorrhagic stroke is a life-threatening disease characterized by a sudden rupture of cerebral blood vessels, and it is widely believed that neural cell death occurs after exposure to blood metabolites or subsequently damaged cells. Neural stem cells (NSCs), which maintain neurogenesis and are found in subgranular zone and subventricular zone, are thought to be an endogenous neuroprotective mechanism for these brain injuries. However, due to the complexity of NSCs and their microenvironment, current strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Brain injuries such as a traumatic injury, stroke, or other neurodegenerative disorders are life-threatening damage and leading causes of death and disability in the population worldwide, with an extensive range of symptoms and disabilities [ 40 42 ]. Brain injury causes neural cell death when the damage occurs and tissue lacks blood oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
“…Brain injuries such as a traumatic injury, stroke, or other neurodegenerative disorders are life-threatening damage and leading causes of death and disability in the population worldwide, with an extensive range of symptoms and disabilities [ 40 42 ]. Brain injury causes neural cell death when the damage occurs and tissue lacks blood oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our study not only identified the brain regions affected by secondary neurological dysfunction after IVH [15][16][17] from a 3D perspective but it also has the potential for us to construct corresponding intervention strategies for acute traumatic brain trauma at the molecular and cellular levels in the distant future.…”
Section: Main 1 Introductionmentioning
confidence: 96%
“…In summary, our study not only identified the brain regions affected by secondary neurological dysfunction after IVH stimulation from a 3D perspective but also allows for the further investigation of driving cell types and molecular pathways, which might benefit the construction of translational intervention strategies for secondary brain injuries after IVH at the molecular and cellular levels in the distant future (20)(21)(22). Finally, our study is available via a web service (www.combio-lezhang.online/3dstivh/home).…”
Section: Introductionmentioning
confidence: 99%